PENGARUH BEBAN KERJA, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT HARINDRA JAYA TRANSPORT SEMARANG - Hesti Setiningrum; Albert Albert; Moeljono Moeljono; Aep Saefullah (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
The purpose of this study is to determine the effect of workload, work environment, and work motivation on employee performance at PT Harindra Jaya Transport Semarang. The research involved a total population and sample of 85 employees, using a saturated sampling technique. Data collection was carried out through questionnaires, and data analysis was conducted using SPSS 26, which included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing with t-tests, and the coefficient of determination (R²) test. The research results show that workload has a partial positive and significant effect on employee performance, with a t-value of 4.269. The work environment variable also has a positive and significant effect, with a t-value of 8.151. Meanwhile, the work motivation variable has no significant effect on employee performance, with a t-value of -0.001 at PT Harindra Jaya Transport.